Erratum to “A Minimax Ordering Policy for the Infinite Stage Dynamic Inventory Problem” - Jagannathan, R. (Management Science, 1979)
In my recent paper “A Minimax Ordering Policy for the Infinite Stage Dynamic Inventory Problem,” Management Sci., Vol. 24, No. 11 (July 1978), pp. 1138–1145, I noticed some errors in the proof of Theorem A.5 in the Appendix which made the proof somewhat incomplete. I have given below a correct version of the proof, mentioning only its main points.